Antithrombotic management and thrombosis rates in children post–liver transplantation: A case series and literature review. (23rd April 2019) - Flynn, Elise; Huang, Joanna Y.; Hardikar, Winita; Herd, Lauren; Hodgson, Alexandra; Monagle, Paul
Abstract: Thrombosis is a major postoperative complication in pediatric liver transplantation. There is marked heterogeneity in prophylactic antithrombotic therapies used, without established guidelines. This review summarizes current worldwide incidence of thrombotic events and compares antithrombotic therapies in children post–liver transplant, with comparison to our institution's experience. Of the twenty‐three articles with sufficient detail to compare antithrombotic regimens, the overall incidence of thrombosis ranged from 2.4% to 17.3%. Incidence of HAT ranged from 0% to 28.1%, of HVT from 0% to 4.7%, of PVT from 1.5% to 11.2%, and of IVC thrombosis from 0% to 2.8%. Re‐transplantation due to thrombosis ranged from 0% to 4.8%. Prophylactic antithrombotic therapies varied between studies, and bleeding complications were infrequently reported. Since 2010, 96 children underwent 100 liver transplants at our institution with thrombosis incidence comparable to international literature (HAT 6%, PVT 5%, IVC 1%, and HVT 0%). Re‐transplantation due to thrombosis occurred in 2% and major bleeding occurred in 10%. The prophylactic antithrombotic therapies used post–liver transplantation in children remain varied. Low rates of thrombosis have been reported with antiplatelet use both with and without anticoagulation. Standard definitions and consistent reporting of bleeding complications are required, in addition to thrombosis rates, so that true risk‐benefit assessment of reported regimes can be understood.